CRITERION (PREDICTIVE) VALIDATION STUDY OF RELIGIOUS SCHEME SCALE - Budiarto, Yohanes (Jurnal Psikologi, 2017)
The purpose of this study was to confirm the factors of Religious Scheme Scale (RSS) using Indonesian Christian student sample. Participants were 230 students (male n= 100, female = 130) with age ranged from 15 â 23 years old (M = 16.8, SD = 1.588). Factor Analysis using Confirmatory Factor Analysis (CFA) was conducted using AMOS 21 did not confirm the 15 â item 3 â factor as proposed by Streib et al. (2010) but 13 â item 3 factor model. The unsatisfactory 2 variables were found in xenosophia sub scale. This study was considered similar to Proiosâ study (2015) in Greece which dropped 2 items from xenosophia sub scale. The predictive validity of RSS showed a good predictor of identity fusion. In conclusion, RSS is satisfactory to be implemented in Indonesian Christian student samples.Â Keyword: Religious Scheme Scale, Factor analysis, Indonesian Christian students sample, predictive validity, identity fusion